(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Cyclone and multisyclone collectors dominate industrial dust abatement thanks to their mechanical robustness, yet the fan power needed to overcome pressure drop (ΔP) can account for 25 – 35 % of a plant’s ventilation load. This study critically reviews and quantifies constructive design modifications that trim specific energy consumption (SEC) without sacrificing collection efficiency (η). A PRISMA-based scoping review of Scopus and Web of Science (January 2023 – May 2025) retrieved 47 papers; 12 high-quality studies met pre-defined inclusion criteria. Key aerodynamic variables were re-calculated and normalised to a Stairmand baseline using Euler (Eu) and power (NP) numbers. Complementary CFD metamodels reproduced the reported geometries to cross-verify ΔP trends. Results show that: (i) secondary vortex finders (SVF) and elliptical bodies achieve ΔP cuts of 30–50 %; (ii) axial-flow cyclones reduce Eu by up to 28 % when optimised for blade angle and exhaust depth; (iii) multi-inlet spirals and draft plates offer 15–25 % savings as low-cost retrofits. Overall, judicious redesign alone can lower SEC by 18 – 45 %, with the greatest gains at Re>2×10⁵. Implementation trade-offs—erosion, scale-up, shifting cut-diameters—are discussed, and a step-wise retrofit roadmap prioritising low-capital measures ahead of full-body replacement is proposed. Future work should integrate ΔP sensors, variable-frequency fans and AI controllers to exploit the reduced resistance dynamically.